Bibliometric analysis of rheumatology research in the Arab countries. (December 2016) - Bayoumy, Karim; MacDonald, Ross; Dargham, Soha; Arayssi, Thurayya
Abstract Background The Arab world has seen an increase in the burden of musculoskeletal diseases. No bibliometric studies have characterized rheumatology research in the Arab world. This study evaluates the productivity and impact of rheumatology research in the Arab world. Methods We searched the Web of Science Core Collection for rheumatology publications, from 1976 to 2014, for each of the Arab League (AL) countries, North America, Europe and Asia. For the AL countries, the overall trend of publications and citations was analyzed, while considering the paper type and collaborations. Results The AL countries published 944 rheumatology papers over the period studied. The number of publications increased by a factor of 2.77 (95 % CI, 2.75–2.78) each decade, and citations increased by a factor of 2.36 (95 % CI, 0.96–5.82). The absolute number of papers included in the top-10 rheumatology journals remained constant but the proportion decreased. Papers involving collaboration among AL countries were found to increase over time. Conclusions Overall, the AL countries lag in research productivity and impact compared to other regions. Three countries are responsible for the majority of publications, while four countries receive the majority of citations.